Characterization of pearls by X-ray phase contrast imaging with a grating interferometer. (November 2016) - Revol, Vincent; Hanser, Carina; Krzemnicki, Michael
Abstract: In this study, X-ray phase contrast imaging with a grating interferometer is applied on pearls for the first time in order to distinguish natural pearls from cultured pearls. Traditionally, this separation is mainly based on X-ray radiography. In order to visualize the internal structure of pearls we used a custom-made grating interferometer setup and performed measurements on three different pearl products, a natural pearl, a beaded cultured pearl and a beadless cultured pearl. To enhance the visibility of the internal pearl structures, we applied a high-pass filter in order to better conclude on the applicability of this technique to the separation of natural and cultured pearls. The study shows that it is possible to visualize internal pearl structures using distinctly shorter exposure times compared to traditional X-ray radiography and that X-ray phase contrast imaging is a promising complementary method for pearl analysis. Highlights: X-ray phase contrast provides a new analytical method for pearl analysis. The method provides improved the detectability of internal details. The new method is faster than most traditional pearl analysis techniques.